2021
DOI: 10.1111/jgs.17230
|View full text |Cite
|
Sign up to set email alerts
|

English and Spanish‐speaking vulnerable older adults report many barriers to advance care planning

Abstract: Background/objectives Advance care planning (ACP) rates are low in diverse, vulnerable older adults, yet little is known about the unique barriers they face and how these barriers impact ACP documentation rates. Design Validated questionnaires listing patient, family/friend, and clinician/system‐level ACP barriers and an open‐ended question on ACP barriers. Setting Two San Francisco public/Department of Veterans Affairs hospitals. Participants One thousand two hundred and forty‐one English and Spanish‐speaking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Regarding ACP burdens, elderly individuals seem to be most concerned that having an ACP discussion may bring bad luck or emotional distress. A US study of 1241 elderly individuals showed that discomfort discussing ACP was the most significant barrier to ACP implementation in the elderly population [ 22 ]. Discussing death and dying is a taboo in Asian culture, particularly Chinese culture.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ACP burdens, elderly individuals seem to be most concerned that having an ACP discussion may bring bad luck or emotional distress. A US study of 1241 elderly individuals showed that discomfort discussing ACP was the most significant barrier to ACP implementation in the elderly population [ 22 ]. Discussing death and dying is a taboo in Asian culture, particularly Chinese culture.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Societal barriers such as distrust, health literacy, and lower education levels contribute to this disparity, reinforcing the importance of individualized approaches to ACP conversations with older adults. [11][12][13] Health care preferences, particularly regarding end-of-life decisions, may shift over time and in changing situations. It is crucial to discuss What Matters throughout the older adult's hospitalization, as needs and priorities change with disease progression, emotional adjustment, and relationship shifts.…”
Section: Assess What Mattersmentioning
confidence: 99%
“…16 the importance of individualized approaches to ACP conversations with older adults. [11][12][13] Health care preferences, particularly regarding end-of-life decisions, may shift over time and in changing situations. It is crucial to discuss What Matters throughout the older adult's hospitalization, as needs and priorities change with disease progression, emotional adjustment, and relationship shifts.…”
Section: Transitioning To Homementioning
confidence: 99%
“…An estimated 60% of older adults have participated in ACP, with lower rates among people of color 11, 12. Societal barriers such as distrust, health literacy, and lower education levels contribute to this disparity, reinforcing the importance of individualized approaches to ACP conversations with older adults 11-13…”
Section: Assess What Mattersmentioning
confidence: 99%